(untitled) (Anclajes, 2022)
Pablo Katchadjian’s experimental novel Qué hacer (2010) is constructed by repetitions that assemble—in an unpredictable and unbridled way—different settings, objects, actions, and characters. It is a fictional force or narrative energy where the living as random power transformation appears. In the context of a dispute around this capacity for variation, this work presents escape, failures, wanderings, excesses, and detotalizations that question modes of subjectivity, temporal orderings, ways of thinking and emotional control, which, in turn, move away from a revolution model. In this way, this article proposes to delineate the resonances of the experimental nature of Pablo Katchadjian’s writing in the context of neoliberalism.